Effects of Selenium Supplementation in Obese Selenocysteine Lyase Knockout Mouse (P24-022-19). (13th June 2019) - Watanabe, Lígia Moriguchi; Hashimoto, Ann; Berry, Marla; Seale, Lucia
Abstract: Objectives: We previously demonstrated that disruption of selenocysteine lyase (Scly) in mice leads to the development of obesity and metabolic syndrome under selenium deficiency, with effects on glucose homeostasis in the liver. It is unknown whether the physiology of skeletal muscle, a key tissue in glucose disposal, is also affected by the disruption of Scly. Here, we investigated the effects of a high-fat diet supplemented with selenium in the muscle physiology of Scly knockout (KO) mice Methods: Age-matched homozygous male and female Scly KO and wild type (WT) from C57BL/6 J background were group-caged and fed for three months to a diet containing 45% kcal fat and 0.25 ppm (adequate) or 1 ppm (high) of selenium as sodium selenite. Serum, liver, soleus, and brown adipose tissue (BAT) were collected and assessed for total glutathione peroxidase (GPX) activity and creatine kinase (CK). Total RNA was extracted from soleus and liver, reverse-transcribed, and used in qPCR. Results: Following an adequate selenium intake, total GPX activity in serum, mRNA of GPX1 and selenoprotein P in the liver, and mRNA of selenoprotein N in soleus were unchanged of Scly KO compared to WT mice, both in males and females. We observed five-fold increase of CK activity in serum and a one-fold decrease in soleus of Scly KO male mice when compared with WT. Increased CK levels in serum have been related with muscle impairment. Interestingly, when male Scly KO mice were fed a high selenium diet, we observed the opposite effect, with serum CK activity significantly decreased, while in soleus CK activity increased in Scly KO mice. CK activity levels on liver or BAT were unchanged. CK activity in serum was unchanged in female mice, corroborating to the previously described sexual dimorphism for these animals. These results suggest an improvement in Scly KO muscle health after selenium supplementation. Conclusions: Adequate selenium levels maintain selenium homeostasis and ensure the maintenance of selenoprotein levels, but high selenium intake may be necessary to preserve muscle health. Funding Sources: FAPESP/Brazil, NIDDK-NIH/USA, NIMHD-NIH/USA.